PENGARUH PEMBELAJARAN ORGANISASI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PERILAKU KERJA INOVATIF PEGAWAI DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL MEDIASI (Studi Pada Dinas Perhubungan Kabupaten Tegal) - Rizkinta Widasti; Ali Mursid (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
A dynamic environment accompanied by the rapid development of science and technology requires every organization to innovate in order to survive and develop better than before, including nirlaba organizations such as the government organization. Dinas Perhubungan Kabupaten Tegal is a government organization thatis identical with a rigid work pattern. However, as one of the organizations that engage in public services,Dinas Perhubungan Kabupaten Tegal is required to be innovative to solve problems, improve performance and provide the best service for the community. This study aims to analyze the effect of organizational learning and transformational leadership on employee innovative work behavior and the role of work engagement as a mediator. The sampling technique that is used in this research is the saturated sample technique of 49 employees. The method of data collection is using questionnaire by distributing it to all employees of Dinas Perhubungan Kab. Tegal who are selected as the samples. Data analysis is carried out using the Partial LeastSquare (PLS) method by using SmartPLS version 3 software. The research results show that organizationallearning and transformational leadership prove significantly to have a positive effect on employee innovative work behavior, and work engagement is proven to be able to mediate the effect of organizational learning andtransformational leadership on employee innovative work behavior. These findings indicate that to improve employee innovative work behavior, it is necessary to have organizational learning, apply transformational leadership and increase work engagement.